Review Artikel Uji Kandungan Estrak Biji Kemiri (Aurites Moluccana L. Willd) sebagai Penumbuh Rambut - Dea Lestari; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In Jambi, research has been conducted on candlenut seed extract which has been proven to be of high quality and has been widely marketed throughout Indonesia. The purpose of this study was to evaluate the effectiveness of candlenut seed extract (Aurites moluccana L.) on various hair problems such as graying and hair loss. This study is a literature study that uses data collection methods from library sources. Secondary data is compiled and analyzed to reach conclusions regarding the topic studied. Candlenut plants (Aleurites moluccana L.) have the potential as hair fertilizers and health care, thanks to the content of saponins, flavonoids, and polyphenols found in seeds, leaves, and roots. The Dayak ethnic group uses burned candlenut fruit for hair care. In addition, candlenuts also function as a medicine for flu and colds, and have anticancer properties. The conclusion of this review is to support the potential of candlenut seed extract as a solution to hair problems However, further research is needed to understand how the active ingredients involved work and to standardize testing methods to ensure the clinical application of the extract's efficacy.